Problematic Social Media Use and Social Connectedness in Adolescence: The Mediating and Moderating Role of Family Life Satisfaction - Savci, Mustafa; Akat, Muhammed; Ercengiz, Mustafa; Griffiths, Mark D.; Aysan, Ferda (Springer, 2022)
Problematic social media use (PSMU) among adolescents has become an area of increasing research interest in recent years. It is known that PSMU is negatively associated with social connectedness. The present study examined the role of family life satisfaction in this relationship by investigating its mediating and moderating role in the relationship between problematic social use and social connectedness. The present study comprised 549 adolescents (296 girls and 253 boys) who had used social media for at least 1 year and had at least one social media account. The measures used included the Social Media Disorder Scale, Social Connectedness Scale, and Family Life Satisfaction Scale. Mediation and moderation analyses were performed using Hayes's Process program. Regression analysis showed that PSMU negatively predicted family life satisfaction and social connectedness. In addition, family life satisfaction and PSMU predicted social connectedness. Mediation analysis showed that family life satisfaction had a significant mediation effect in the relationship between PSMU and social connectedness. Family life satisfaction was partially mediated in the relationship between PSMU and social connectedness. Moderation analysis showed that family life satisfaction did not have a significant effect on the relationship between PSMU and social connectedness. The study suggests that family life satisfaction is a meaningful mediator (but not a moderator) in the relationship between problematic social media use and social connectedness.
Keywords: Problematic social media use; Social networking; Social connectedness; Family life satisfaction; Mediation analysis; Moderation analysis; Adolescence